A taxonomic contribution to the genus Pseudovelia Hoberlandt, 1951 (Hemiptera: Veliidae) from China, with descriptions of ten new species - Ye, Zhen; Polhemus, Dan A.; Bu, Wenjun (Zootaxa, 2013)
Thirteen species of the genus Pseudovelia Hoberlandt are now known from China. Of these, P.longitarsa Andersen, 1983 is the only member of the genus previously recorded from China. P. pusilla Hecher, 1997 and P. tibialis tibialis Esaki & Miyamoto, 1955 are previously described species newly recorded from China. In addition, 10 new species are described as follows: P. anthracina sp. n., P. contorta sp. n., P. extensa sp. n., P. fulva sp. n., P. globosa sp. n., P. hsiaoi sp. n., P. longiseta sp. n., P. piliformis sp. n., P. taiwanensis sp. n., P. vittiformis sp. n. Photographs of the male dorsal habitus, male forelegs, male middle legs, male hind legs, male hind tarsal details and male genitalic structures are provided, accompa-nied by line drawings of male genitalic structures and a distribution map for all Chinese Pseudovelia species. A key to the males of all 13 Chinese Pseudovelia species is also provided to assist in future identification.